2018
DOI: 10.1007/s00604-017-2640-2
|View full text |Cite
|
Sign up to set email alerts
|

Selective adsorption and determination of hexavalent chromium ions using graphene oxide modified with amino silanes

Abstract: Novel adsorbents are described for the preconcentration of chromium(VI). Graphene oxide (GO) was modified with various amino silanes containing one, two, or three nitrogen atoms in the molecule. These include 3-aminopropyltriethoxysilane (APTES), N-(3-trimethoxysilylpropyl)ethylenediamine (TMSPEDA), and N1-(3-trimethoxysilylpropyl)diethylenetriamine (TMSPDETA). The resulting GO derivatives were characterized by scanning electron microscopy, X-ray photoelectron spectroscopy, and energy-dispersive X-ray fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(37 citation statements)
references
References 35 publications
1
33
0
2
Order By: Relevance
“…A dose of 1 g L À1 of each adsorbent was used to treat 25 mL solution of 60 mg L À1 Cr(VI) at pH 2 for 60 min at 30 C. Pure GO QDs exhibit small values of R% and q of 77.7% and 46.64 mg g À1 , respectively, for the adsorption of Cr(VI) through electrostatic interactions coupled with Cr(VI) reduction to Cr(III) and followed by Cr(III) complexation. 48,54 At a low pH value of 2, the removal of Cr(VI) in the aqueous phase is faster since the negatively charged Cr(VI) species migrate to the positive surface of the GO QDs (protonated hydroxyl groups and carbonyl groups) with the help of electrostatic driving forces. Cr(VI) reduction to Cr(III) by contact with the electron-donor groups of GO QDs (OH À groups) occurs during the adsorption process and the reduced Cr(III) remains in the aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…A dose of 1 g L À1 of each adsorbent was used to treat 25 mL solution of 60 mg L À1 Cr(VI) at pH 2 for 60 min at 30 C. Pure GO QDs exhibit small values of R% and q of 77.7% and 46.64 mg g À1 , respectively, for the adsorption of Cr(VI) through electrostatic interactions coupled with Cr(VI) reduction to Cr(III) and followed by Cr(III) complexation. 48,54 At a low pH value of 2, the removal of Cr(VI) in the aqueous phase is faster since the negatively charged Cr(VI) species migrate to the positive surface of the GO QDs (protonated hydroxyl groups and carbonyl groups) with the help of electrostatic driving forces. Cr(VI) reduction to Cr(III) by contact with the electron-donor groups of GO QDs (OH À groups) occurs during the adsorption process and the reduced Cr(III) remains in the aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we showed that the adsorbents synthesized by chemically bonding GO and amino-silanes have excellent performance in chromium adsorption (260.74 mg g −1 ) 25 . However, in the similar work by Janik et al (2018), adsorbents have relatively low Cr(VI) adsorption capacities (13.3-15.1 mg g −1 ) and the opposite order of Lee et al (2020)'s 28 . The minor yet remarkable difference between these two studies, which many researchers overlooked, is the use of different approaches for the preparation of GO.…”
mentioning
confidence: 84%
“…Thus, TXRF is a suitable method for determining uranium in liquid samples by using U L X‐ray lines when uranium is separated from rubidium. Recently, graphene‐based materials, which are new carbon‐based materials that are of interest in separation science, are used in solid phase extraction to measure trace metal ions . Graphene has extraordinary properties, including nanosize, high surface area, thermal and chemical stability, and excellent adsorption affinity to metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, graphene-based materials, which are new carbon-based materials that are of interest in separation science, are used in solid phase extraction to measure trace metal ions. [26][27][28][29][30][31][32] Graphene has extraordinary properties, including nanosize, high surface area, thermal and chemical stability, and excellent adsorption affinity to metal ions. These properties have led to graphene-based material becoming a desirable adsorbent in a popular sample preparation technique known as solid phase extraction.…”
Section: Introductionmentioning
confidence: 99%